Using Free4talk Application to Improve Students’ Speaking Skill - Mustasyfa Thabib Kariadi; Elvah Fathin Alfairuza; Novita Pri Andini (Jurnal Vokasia, 2025)
This research aims to investigate the difficulties sixth-grade elementary school students face in improving speaking and the effectiveness of utilizing the Free4talk application in improving their speaking skills. Identified issues include lack of time for English practice, feelings of embarrassment lack of confidence in pronunciation, and limited vocabulary in English. This research used a pre-experimental method with a purposive sampling technique. The research was conducted on grade 6th students at SD Al Furqoon in the Academic Year of 2023/2024, with a total sample are 22 students. The research instruments to collect the data included a questionnaire, pre-test, post-test, and observation. Identified issues include lack of time for English practice, feelings of embarrassment lack of confidence in English pronunciation, and limited vocabulary in English. This is evident from the F value of 1.286 and sig=0.000, which means <0.05, this implies that there is an influence from the implementation of the Free4talk application on language speaking skills. For the second question, the researcher found the formula d(f) = n-2, resulting in a calculated d(f) value of 20 and the result of testing the variables of Free4talk application implementation (X) and improvement of speaking skills (Y) above supported by Cronbach’s Alpha values generated successively of 0.737 and 0.819. The findings indicate a significant improvement in students’ speaking skills after using the Free4talk application. Statistical analysis reveals a significant value indicating a meaningful impact of implementing the Free4talk application on students’ language-speaking skills. In conclusion, the utilization of the Free4talk application in enhancing the speaking skills of sixth-grade elementary school students is quite effective. This suggests that the application can be a beneficial tool in English language learning at the elementary level.